Effectiveness of avatar-delivered instruction on social initiations by children with Autism Spectrum Disorder. (March 2020) - Charlton, Cade T.; Kellems, Ryan O.; Black, Brooke; Bussey, Heidi C.; Ferguson, Rachel; Goncalves, Bruna; Jensen, Mikaela; Vallejo, Sara
Highlights: This study evaluated the use of a live animation avatar to teach five individuals with autism to initiate conversations. The use of an avatar with explicit instruction was effective and preferable to participants and their parents. Participants generalized the use of the acquired skill to interactions with peers. Avatars are more dynamic than some applications of technology-aided instruction and may be equally effective. Abstract: Background: Individuals with autism often struggle to establish and maintain positive relationships with peers and adults due to communication and social difficulties. Reviews of the research literature on social skills curricula suggest these approaches may be less than effective and often fail to promote generalization of acquired skills. Advances in the availability and adaptability of live animation and digital avatars could provide interventionists a tool to maximize engagement during instruction and program for generalization. The purpose of this study was to examine the effects of an avatar-based social skills intervention on participants' social initiations in a clinical setting and with same-age peers. Method: The research team used a nonconcurrent multiple baseline design to evaluate the effects of instruction from an avatar on students' social skills. Systematic direct observation and the Social Skills Improvement System were used to evaluate the effects of an avatar delivered social skills lesson. Social validity was measured from the perspective of both participants and their parents. Results: Following instruction from an avatar, participants' percentage of independent steps completed in the skill "starting a conversation" increased to consistently above 80 %, or above typical mastery levels. Participants' conversation skills generalized to interactions with same-age peers. Finally, parents reported small positive gains in social skills, and participants indicated the intervention was socially valid. Conclusions: The findings from this study support the use of technology-aided interventions and instruction, specifically the use of live animation avatars. Future studies could extend use of this technology beyond the relatively simple, yet effective, application described here.